Multi-Objective Optimization for Structural Parameters of Swing-Compliant Hook - GE Shicheng, GUO Zhuoyu, LIANG Xi, MO Zonglai, LI Jun (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
To solve the problems of alignment for launch container loading in field-artillery rocket, a novel end-effector, i.e., a swing-compliant hook, is proposed, whose structural parameters are optimized. First, the theoretical model describing the performance of the swing-compliant hook is established based on the node displacement method. The static displacement, static stress, and swing curve of the swing-compliant hook are analyzed by MATLAB, which verifies the rationality of the model. Then, the main structure parameters on the performance of the swing-compliant hook are obtained by using the experimental design method. Additionally, a response surface model characterizing the comprehensive performance of the swing-compliant hook is established. The optimization results show that when the length and the installation height of the compliant mechanism are 90 mm and 23 mm, and the end height of the lifting hook is 110 mm, the swing-compliant hook has an excellent performance in docking, lifting, transferring, and locating.